Conserve My Village—Finnish, Norwegian and Swedish Students’ Valued Landscapes and Well-Being - Yli-Panula Eija; Jeronen Eila; Matikainen Eila; Persson Christel (MDPI, 2022)
In the context of landscape, both the natural environment and the built environment can be linked with human health and well-being. This connection has been studied among adults, but no research has been conducted on young people. To fill this gap, this case study aimed to elucidate students’ views on landscapes worth conserving and the landscapes that affect and support their well-being. The participants (n = 538) were Finnish, Norwegian and Swedish students from grades 3–6. The students drew the landscapes they wanted to conserve. The drawn landscapes and the welfare-supporting features they contained were analysed using inductive and abductive content analyses. The students from all three countries preferred water, forest and yard landscapes. In the drawings of natural landscapes, the most recurring themes were sunrise or sunset, forest, beach and mountain landscapes. Physical well-being was manifested in the opportunity to jog and walk. Social well-being was reflected in the presence of friends, relatives and animals. Therapeutically important well-being-related spaces—the so-called green (natural areas), blue (aquatic environments) and white (e.g., snow) areas—were also depicted in the participants’ drawings. It can be concluded that the drawn landscapes reflect several values that promote students’ well-being.